Study of prevalence, etiology, response to treatment and outcome of paediatric shock in a tertiary care hospital - Gobinathan, S.; Kannan, K. Suresh (International Journal of Contemporary Pediatrics, 2018)
Background: Shock accounts for 2% of children admitted to Paediatric casualty worldwide as per most western literature and in Nelson text book of Paediatrics. About 10 million children die of shock every year in the world. Highest mortality is observed in under 5 children in developing countries. Clinical manifestations are due to decreased perfusion to tissues, the compensatory mechanisms that are triggered by the decreased perfusion and the inadequate removal of metabolic wastes. This study was carried out to assess the prevalence of paediatric shock in children admitted to Paediatric ICU, to identify possible aetiology and the response to treatment and outcome in patients admitted with shock in Paediatrics Department of Government Mohan Kumaramangalam Medical College, Hospital, and Salem. Methods: All sick children admitted to Paediatric intensive care unit of Government Mohankumaramangalam Medical College Hospital, Salem with the suspicion of shock are assessed by using the rapid cardiopulmonary assessment and diagnosed suffering from shock. Possible etiology, type and severity of shock would be arrived at using a targeted history, clinical examination and relevant laboratory investigations. Results: All children who had unstable airway or bradypnea, were having decompensated shock and except one among them all expired despite prompt airway management. Respiratory distress noticed in 23 (40.4%) of children and all of them had either cardiogenic, septic shock or a combination of both. Capillary refill time was prolonged in 52 (91.2%) of children and the remainder 5 (8.8%) had flash refill and managed as warm septic shock. Decompensated shock as evidenced by low blood pressure was seen in 57.9% children. All of them had altered mental status. Urinary output was monitored in 38 children of which 31 (81.6%) had oliguria. Conclusions: Septic shock accounts for majority of decompensated shock and poor outcome to management. Infancy decompensated shock, septic shock and those requiring ventilator support were the factors influencing the outcome of management.